Employee green innovation behavior based on the ability-motivation-opportunity framework: fuzzy-set qualitative comparative analysis - Ma, Yonggang; Wang, Jiaojiao (Frontiers in Sustainability, 2024)
Purpose: The increasing emphasis on ecological responsibility within Chinese enterprises has underscored the critical role of employees' green innovation behavior in enhancing environmental performance and enhancing core competitiveness. Grounded in the Ability, Motivation, and Opportunity (AMO) theoretical framework, this study employs configuration analysis to investigate the driving mechanisms behind the multi-factorial interplay affecting employees' green innovation behaviors.Methodology: Data was collected through questionnaires distributed among a random sample of 219 Chinese corporate employees. Fuzzy-set Qualitative Comparative Analysis (fs-QCA) was then applied to identify the specific configurations contributing to high levels of green innovation behavior.(1) There are three driving paths for employees' green innovation behaviors: a leadershiporganization co-driving path composed of green self-efficacy, environmentally transformative leadership, and organizational support; a leadership-driving path composed of green self-efficacy, environmentally transformative leadership, internal motivation, and external motivation; and an organization-driving path composed of green self-efficacy, organizational support, internal motivation, and external motivation.. (2) There are three non-green innovation behavior-driven paths: they are divided into organizational support lack type, leadership-organizational joint lack type, and capability lack type. (3) Under specific conditions, motivational factors and environmental change leadership, motivational factors and sense of organizational support can promote employees' green innovation through equivalent substitution.Originality: (1) Significant emphasis is placed on examining how Ability, Motivation, and Opportunity synergize to shape employees' green innovation behaviors, addressing a gap in the literature regarding their collective influence. (2) The study applies a configural approach to unravel the complex causal linkages influencing employees' green innovation behaviors, offering detailed insights into the dynamics between individual attributes and contextual factors. (3) This research elucidates the combined effects of factors such as organizational support, leadership styles, and employees' intrinsic and extrinsic motivations, and how they collaborate to foster an environment conducive to green innovation. Implications: The findings not only enrich the theoretical understanding of green innovation behavior but also provide strategic recommendations for Chinese enterprises to encourage such behavior. These insights are essential for guiding sustainable development and enhancing competitive advantage.